SELF-ESTEEM REMAJA AWAL: TEMUAN BASELINE DARI RENCANA PROGRAM SELF-INSTRUCTIONAL TRAINING KOMPETENSI DIRI - Dilla Tria Febrina; Puji Lestari Suharso; Airin Yustikarini Saleh (Departemen Psikologi Universitas Pendidikan Indonesia, 2018)
This research aimed to obtain baseline data as the first stage of preparation of self-instructional training programs as an intervention for early adolescents who had self-esteem problems. The participant in this study was a teenage boy who has a negative self-evaluation related to self-competence at school. The design in this research was single-subject, with A1-A2-A3 design. Measurement of self-esteem in this study was interview techniques on the participant, significant other, and teachers among three different situations. The instrument was developed based on high self-esteem characteristics of Rosenberg and Owens (Guindon, 2010). The results of this study indicated that the boy had low self-esteem related to self-competence and affected to important areas of development such as academic. Based on this study, further researchs was necessary to develope an intervention that solved the problems of self-esteem in early adolescence.